1988
DOI: 10.1007/bf03184883
|View full text |Cite
|
Sign up to set email alerts
|

Ethical frameworks of “Tomorrow’s Business Leaders”

Abstract: 65This research explores the influence of five ethical frameworks on business students' decision regarding the resolution of an ethical dilemma in a simulation. The frameworks of ethical tests are: Utilitarianism (the greatest goodfor the greatest number); Self-Interest (maximizing the benefits to the individual); Categorical Imperative (universal principles ofmorality); Legality (rules, laws, etc.); and Light of Day (possibility of one's actions being discovered). Results showed that the strongest influences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…The older managers' focus may be broader, corresponding to a higher stage, whereas younger managers may focus more narrowly, corresponding to lower cognitive stages of moral reasoning. Dahl, Mandell, and Barton (1988) also examined the effects of this demographic variable on ethical decision making. They found that age was the only factor that was significantly related to ethical decision making.…”
Section: Agementioning
confidence: 99%
“…The older managers' focus may be broader, corresponding to a higher stage, whereas younger managers may focus more narrowly, corresponding to lower cognitive stages of moral reasoning. Dahl, Mandell, and Barton (1988) also examined the effects of this demographic variable on ethical decision making. They found that age was the only factor that was significantly related to ethical decision making.…”
Section: Agementioning
confidence: 99%
“…AI Ethical Principles are those used in the e-ERM framework [40]. In addition, the frequency of use of the underlying ethical lenses was assessed, namely, fairness/justice [41,42], duty [43], virtue ethics [42,44], common good [42], utilitarian [42,44,45], and rights [42,44,45]. The level of the implementation of the AI Ethical Principles was probed, considering if they were "Documented," "Published," "Training provided," or "Enforced and monitored.…”
Section: A Survey Questionsmentioning
confidence: 99%